77.4k views
0 votes
-6x^3+3x^2-4 divide 2x-3 remainder theorem

User Mouwsy
by
5.8k points

1 Answer

6 votes

1. Multiply
2x-3 by
-3x^2 to get
(2x-3)\cdot (-3x^2)=-6x^3+9x^2.

2. Subtract
-6x^3+9x^2 from the polynomial
-6x^3+3x^2-4. You obtain


-6x^2-4.

3. Multiply
2x-3 by
-3x:


(2x-3)\cdot (-3x)=-6x^2+9x

and subtract it from the polynomial
-6x^2-4.

The result is
-9x-4.

4. Multiply
2x-3 by
-(9)/(2):


(2x-3)\cdot \left(-(9)/(2)\right)=-9x+(27)/(2)

and subtract it from
-9x-4. The result is


-4-(27)/(2)=-(35)/(2)=-17.5.

5. After division you get


-6x^3+3x^2-4=(2x-3)\cdot (-3x^2-3x-4.5)-17.5.

User Rockyraw
by
5.2k points